A comparative study of sociological thoughts of Ibn Khaldun and Ali Shari'ati with special reference to al-Muqaddimah and on the sociology of Islam - Zuraida Abd Rahim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study analyses and compares two important works of two prominent Muslim scholars of different periods - one classical and the other contemporary. The works are Al-Muqaddimah by Ibn Khaldun and On the Sociology of Islam by Ali Shari'ati. The two works provide evidence for a comparative sociological thought of the two thinkers who have different cultural backgrounds and orientations. Specifically, the study was undertaken to achieve three main objectives: 1) to compare the sociological thought of Ibn Khaldun and Ali Shari'ati based on their selected works, 2) to produce a synthesized thought on ideal society based on the views of these two thinkers and 3) to analyse the influence of their respective social environment in shaping their sociological thoughts. These objectives were achieved by answering three corresponding research questions: 1) What are the differences and similarities in the thought of Ibn Khaldun and Ali Shari'ati? 2) What theory of ideal society can be derived from the views of these two thinkers? and (3) In what way have their social environments influenced their thought? Methodologically, the study followed 'The Ten Steps Content Analysis' technique in drawing comparison and identifying the differences and similarities between the two respective scholars as detailed in the Methodology Chapter. In generating their synthesized thought, the study was inspired by the approach employed by McNelis (1972) in one of his works. In terms of findings, the research has found that there are aspects which are peculiar to each of the thinker such as their scientific and philosophical approaches in constructing their views and thought as reported in the Findings Chapter. More importantly, the study found significant commonalities between the two, particularly in terms of their interest in social philosophy, which consequently shed light on their respective sociological thoughts. The findings also showed that there were significant influences of their respective academic, socio-cultural and religious backgrounds on their thoughts. In conclusion, Ibn Khaldun can be said to have provided a scientific floor for Ali Shari'ati to build his metaphysical ceiling for his sociological thought. Some recommendations and suggestions for future study are also proposed at the end of this dissertation.